The advantage of rebranding food and beverage business / Nurelyza Shaheera Anwar Fuad - Anwar Fuad, Nurelyza Shaheera (2022)
Rebranding is about an identity that sets apart from the competition and present the memorable impression and give an advantage to refreshing the look and feel with the ability to reach others. The purpose of this study is to focus on the advantage of rebranding food and beverage business. Every company has an identity but some company facing such fears to undertake the effort or rebrand. It demands internal reflection and a level of self-awareness, as a successful rebrand takes about the existing brand to be proceed as more of an evolution. To obtained information for this study, researcher used quantitative method to get respondent from target audience regarding to the issue. Researcher also used secondary data such as books, journals, articles, news and internet sources. This research will examine on how rebranding can be as advantages of food and beverages business to stay ahead from other competitors. At the end of this study, that rebranding has positive effects on consumer perceptions and can be used as a marketing tool in order to gain competitive advantages.